Tenure through Tyranny? Repression, Dissent, and Leader Removal in Africa and Latin America, 1990–2006. Issue 1 (13th September 2021) - Davenport, Christian; RezaeeDaryakenari, Babak; Wood, Reed M
Abstract: With few exceptions, prior research on leadership survival focuses largely on state institutional characteristics or economic context. We shift this orientation by explicitly considering the important role contentious interactions between the incumbent regime and dissident actors play in determining the duration of leader tenure as well as the manner in which a leader is removed. Specifically, we focus on the severity of the incumbent leader's response to dissident challenges. We contend that the severity of this response represents a critical signal which informs the decisions of specific audiences that ultimately determine the incumbent's survival. To evaluate our argument, we employ detailed information on dissent–repression dynamics and leader survival for a leader-month sample of 69 African and Latin American states between 1990 and 2006. Our results suggest that incumbents are vulnerable to coup d' état when government repression is perceived as weaker than would normally be expected for a given challenge. By contrast, removal via revolution becomes increasingly likely when repression dramatically exceeds the levels that would normally be warranted given the extant challenge.